Mechanical structures for electronic equipment. Thermal management for cabinets in accordance with IEC 60297 and IEC 60917 series. Design guide. Evaluation method for thermoelectrical cooling systems (Peltier effect) Part 3, (28th February 2010) - British Standards Institution
No abstract available